Study the Effect of Deposition Location on the Optical Properties of CuO Absorption Layer Prepared by Fully Computerized Spray Pyrolysis Deposition - Essa, Mohammed Sh.; Chiad, Baha T. (Iraqi Journal of Science, 2022)
The Topography, Physical and Optical properties of as-deposited copper oxide CuO absorption layer sprayed using homemade fully computerized CNC spray pyrolysis deposition technique at different deposition speed are reported. These layers are characterized by UV-Visible spectrophotometer, optical microscope, and thickness monitor studies. The optical transmittance study indicates that these layer exhibit high absorption coefficient in the visible range. The optical band gap is found to be at about at speeds (3,6 mm/s). Better homogeneity in CuO layer is found at the speed 5 mm/s. The film thickness lies within the 129-412 nm range.